Differences between Android and iPhone users in their security and privacy awareness - Reinfelder, Lena; Benenson, Zinaida; Gassmann, Freya (TrustBus, 2014)
This work compares Android and iPhone users according to their security and privacy awareness when handling apps. Based on an online survey conducted with over 700 German respondents (mostly university students) we found out that Android users seem to be more aware of the risks associated with the app usage than iPhone users. For example, iPhone users almost never consider the possibility of apps sending premium-rate SMS or causing other hidden costs. Furthermore, Android users more often mention security, trust and privacy issues as important factors when they decide to use a new app. We hypothesize that the cause of these differences they are likely to arise through differences in app market policies, in app review processes and in presentation of data usage by the apps. © 2014 Springer International Publishing.
UnivIS-Import:2015-04-17:Pub.2014.tech.IMMD.lehrst.differ
Keywords: Android; iOS; privacy awareness; security awareness; Smartphone